2005
DOI: 10.1177/0269881105056647
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of olanzapine on serum levels of ghrelin, adiponectin and leptin in patients with schizophrenia

Abstract: Although treatment with antipsychotics, particularly olanzapine and clozapine, has been implicated in weight gain and higher incidence of diabetes, the mechanism of these adverse reactions remains unclear. The purposes of this study were to explore the early effects of olanzapine on serum levels of ghrelin, adiponectin and leptin, three recently identified hormones that play crucial roles in the regulation of energy balance and glucose metabolism. Thirteen patients with schizophrenia who had not received any m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 33 publications
0
48
1
4
Order By: Relevance
“…30,32 As ghrelin levels are known to be influenced by obesity levels, 33 this indicates that the effect of OLA on ghrelin levels is independent of weight gain. Nevertheless, clinical findings are not entirely consistent, as other authors have reported decreased levels of ghrelin, [34][35][36][37][38] especially after short-term treatment with OLA.…”
Section: Discussionmentioning
confidence: 74%
“…30,32 As ghrelin levels are known to be influenced by obesity levels, 33 this indicates that the effect of OLA on ghrelin levels is independent of weight gain. Nevertheless, clinical findings are not entirely consistent, as other authors have reported decreased levels of ghrelin, [34][35][36][37][38] especially after short-term treatment with OLA.…”
Section: Discussionmentioning
confidence: 74%
“…Previous cross-sectional studies found both higher (Togo et al, 2004) and lower (Richards et al, 2006) adiponectin levels in patients treated with olanzapine compared to healthy controls as well as lower levels in untreated patients compared to controls (Cohn et al, 2006). One additional study found no change in adiponectin after 4 weeks of olanzapine treatment (Hosojima et al, 2006). Similarly, IL-6 levels were elevated in patients with schizophrenia compared to controls but appeared unchanged after 12 weeks of risperidone treatment (Zhang et al, 2004b).…”
Section: Introductionmentioning
confidence: 92%
“…As patients gained substantial amounts of weight on clozapine and olanzapine, serum leptin also rose, but neither weight nor leptin changes were seen in patients exposed to haloperidol or in those who did not receive antipsychotic medication (Kraus et al, 1999). Numerous subsequent prospective trials of olanzapine-treated patients (Eder et al, 2001;Graham et al, 2005b;Ebenbichler et al, 2005;Murashita et al, 2005;Hosojima et al, 2006) and clozapine-treated patients (Monteleone et al, 2002;Kivircik et al, 2003;Sporn et al, 2005;Theisen et al, 2005) confirmed the association between use of these medications, weight gain, and increased serum leptin levels. For agents with less weight gain liability, such as high potency typicals (Hagg et al, 2001;Atmaca et al, 2003a;Atmaca et al, 2003c), sulpiride (Baptista et al, 2000), quetiapine (Atmaca et al, 2003c), or risperidone (Fitzgerald et al, 2003;McIntyre et al, 2003;Martin et al, 2004;Chiu et al, 2006), comparative trials noted modest weight gain and leptin changes, while olanzapine and clozapine exposed subjects experienced marked increases in adiposity, weight and serum leptin.…”
Section: Leptin Drug Effectsmentioning
confidence: 97%
“…Several antipsychotic studies measured metabolic outcomes along with serum leptin levels, but did not specifically calculate correlation coefficients between leptin and other parameters (Baptista et al, 2001;Eder et al, 2001;Atmaca et al, 2003a;Melkersson and Dahl, 2003;Graham et al, 2005a;Graham et al, 2005b;Smith et al, 2005;Sporn et al, 2005;Chiu et al, 2006;Hosojima et al, 2006;Atmaca et al, 2007). Nonetheless, in many instances leptin levels increased significantly without significant changes in serum insulin, other glycemic or lipid measures (Zhang et al, 2004;Murashita et al, 2005;Sporn et al, 2005;Chiu et al, 2006;Hosojima et al, 2006;Atmaca et al, 2007). One cross-sectional study in bipolar subjects also found no correlation between any glucose or lipid parameter and leptin levels (Gergerlioglu et al, 2006), although a small number reported significant correlations between leptin and serum insulin (Baptista et al, 2000;Melkersson et al, 2000;Melkersson and Hulting, 2001), glucose (Wang et al, 2006) and serum triglycerides (Atmaca et al, 2003c); however, most of the authors reporting significant correlations did not control for BMI.…”
Section: Other Metabolic Parametersmentioning
confidence: 99%